Telemonitoring of Daily Activity and Symptom Behavior in Patients with COPD - Tabak, Monique (Hindawi Publishing Corporation, 2012)
Objectives. This study investigated the activity behavior of patients with COPD in detail compared to asymptomatic controls, and the relationship between subjective and objective activities (awareness), and readiness to change activity behavior. Methods. Thirty-nine patients with COPD (66.0 years; FEV(1)% predicted: 44.9%) and 21 healthy controls (57.0 years) participated. Objective daily activity was assessed by accelerometry and expressed as amount of activity in counts per minute (cpm). Patients' baseline subjective activity and stage of change were assessed prior to measurements. Results. Mean daily activity in COPD patients was significantly lower compared to the healthy controls (864 ± 277 cpm versus 1162 ± 282 cpm, P < 0.001). COPD patients showed a temporary decrease in objective activities in the early afternoon. Objective and subjective activities were significantly moderately related and most patients (55.3%) were in the maintenance phase of the stages of change. Conclusions. COPD patients show a distinctive activity decrease in the early afternoon. COPD patients are moderately aware of their daily activity but regard themselves as physically active. Therefore, future telemedicine interventions might consider creating awareness of an active lifestyle and provide feedback that aims to increase and balance activity levels.